Inovasi Bioslurry Refill untuk Penguatan Ekonomi Kelompok Tani Jaya Abadi Gunung Tangis - Sri Ratna Triyasari; Nurul Hidayati; Choirul Umam; Zaky Aditya; Muhammad Nur Fa'id (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
The farmer empowerment program through the Bioslurry Refill innovation was implemented to address the low utilization of livestock waste in Dusun Gunung Tangis, Rek Kerrek Village, Pamekasan. The program integrated Participatory Rural Appraisal (PRA), technical production training, and the development of a refill-based organic fertilization business model. Interventions included technology dissemination, installation of bioslurry handling facilities, training in production and packaging, and assistance in distribution. The results indicate improved farmer knowledge and perceptions regarding biogas technology and the use of bioslurry as an organic fertilizer, reflected in the growing interest in applying bioslurry to agricultural fields. The Jaya Abadi Farmer Group demonstrated the ability to independently manage bioslurry, covering collection, storage, and distribution processes. Barter and cash transaction models were successfully developed according to commodity characteristics, while the Bio Refill system expanded accessibility, strengthened user loyalty, and created microenterprise opportunities at the village level. Institutional support through village mandates further enhanced distribution governance and the sustainability of organic fertilization practices. Overall, the findings show that bioslurry serves not only as a waste management solution but also as an instrument for strengthening the local economy and promoting environmentally friendly agricultural practices.